2022
DOI: 10.1097/sap.0000000000003208
|View full text |Cite
|
Sign up to set email alerts
|

Finger Reconstruction With Distally Based Dorsal Metacarpal Flaps

Abstract: BackgroundDistally based dorsal metacarpal flaps for the reconstruction of finger soft-tissue defects are classified into 3 categories: dorsal metacarpal artery perforator flap, reverse dorsal metacarpal artery (RDMA) flap, and extended reverse dorsal metacarpal artery (ERDMA) flap. The present systematic review aimed to evaluate differences in the outcomes of commonly encountered defects and postoperative complications among these three flaps.MethodsPubMed, Scopus, and Web of Science were systematically searc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 24 publications
(57 reference statements)
0
1
0
1
Order By: Relevance
“…In this respect, Shimbo et al [39] reported that the dorsal metacarpal artery perforator flaps were versatile options for covering proximal to the middle phalanx and distal to the distal interphalangeal joint. This was associated with a lower rate of short-term consequences.…”
Section: Discussionmentioning
confidence: 99%
“…In this respect, Shimbo et al [39] reported that the dorsal metacarpal artery perforator flaps were versatile options for covering proximal to the middle phalanx and distal to the distal interphalangeal joint. This was associated with a lower rate of short-term consequences.…”
Section: Discussionmentioning
confidence: 99%
“…Фетальні оперативні втручання в ділянці кисті, як ніякі інші операції, вимагають докладного топографоанатомічного обґрунтування і всебічних даних з варіантної анатомії артеріальних судин кисті [10][11][12], зокрема тильної поверхні, впродовж плодового періоду онтогенезу людини. Тому, відомості стосовно вікової та індивідуальної анатомічної мінливості артеріальних судин тильної ділянки кисті у плодів людини мають важливе науково-практичне значення для тлумачення істинного напрямку процесів фетального морфогенезу кисті за умов норми.…”
unclassified